Promosi Air Terjun Tangsi 3 Di Solok Selatan - Riski Ramadhan; Defrizal Saputra (Lembaga Pengembangan Kinerja Dosen, 2023)
Tourism is a sector that can be considered profitable and also has the potential for an area to be developed into an asset that is used as a source of production for the region or the country itself. South Solok Regency is one of the regencies in West Sumatra Province, which is one of the prima donna of tourism in this province. Solok Selatan Regency itself is given a quite unique tagline, namely The Heart of Minangkabau. Giving the tagline really represents what the district has. Starting from a variety of tourist and cultural destinations in it. But there are not a few tours in South Solok Regency that have not been exposed by the Tourism Office, one of which is the Tangsi 3 Waterfall Tour. Tangsi 3 Waterfall is located in a tropical rain forest area which has a natural charm that is still beautiful. This waterfall is one of the hidden paradises that this district has.